PENGEMBANGAN PERANGKAT PENILAIAN KINERJA PESERTA DIDIK PADA MATERI POKOK SISTEM EKSKRESI - Sri Mukminati Nur (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2015)
This research aimed (1) to know the development phases of assesment devices of students’ performanceon excretion system; (ii) to identify the quality of the assesment devices performance on excretion system observed from the validity. This is a research and development study by using development model of formative research type. It used one class as a subject of the research with the number of 40 Students and one class as a small group as much 20 students. Then instrument were in the form of validation sheet which is used to get data of the practically and psychomotor assesment, instrument sheet of performance and validity toget data of practically data as well as sheet of the students’ performance assignment to see the level of assignments’ difficulty and distinguishing power.  The result showed that the assesment devices of performance on excretion system has meet the quality criteria of learning devices are valid,the  mean score of  validity for the lessin plan is 3.47 (valid), students’ text  book is 3.44 (valid), students’ worksheet is 3.52 (precisely  valid),. Score of validity are; (i) student’s worksheet by score validation 0,97 (ii) assesment devices of students’ performance assignment by score validation 0.87. therefore, it can be concluded that assesment development devices of students’ performance on excretion system by using the formative research model of development through three phases, namely self evaluation, prototyping, and field test have meet the criteria of valid, reliable, practical, level of difficulty and distinguishing power.